2017
DOI: 10.1080/00223980.2017.1405903
|View full text |Cite
|
Sign up to set email alerts
|

Buffers or Boosters? The Role of HRM Practices in Older Workers' Experience of Stereotype Threat

Abstract: Building on the social identity approach and the HRM literature, this two-wave cross-sectional study examined the effects of negative age-based metastereotypes on the age-based stereotype threat experience of older workers and on organizational disidentification. The moderator role of HRM practices in the relationship between negative age-based metastereotypes and age-based stereotype threat was also investigated. Older workers survey results (n = 469) from 14 manufacturing companies indicated that negative ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…AIHRP have previously been demonstrated to play a significant role in the context of aging workforces (Oliveira and Cabral-Cardoso, 2018; Taneva and Arnold, 2018). However, little is known about the underlying processes that account for the link between HR practices and the thriving of older workers.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…AIHRP have previously been demonstrated to play a significant role in the context of aging workforces (Oliveira and Cabral-Cardoso, 2018; Taneva and Arnold, 2018). However, little is known about the underlying processes that account for the link between HR practices and the thriving of older workers.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, unlike focus on opportunities, perceived remaining time did not mediate the relationship between AIHRP and vitality. This difference can be explained in part by the energy depletion caused by negative views of older workers (Oliveira and Cabral-Cardoso, 2018) which, operating in tandem with declines in perceived remaining time (Rudolph et al , 2018), is likely to cancel out the anticipated positive effects of remaining time on vitality. This is in line with prior evidence, which indicated that remaining time is typically more weakly related – or even unrelated (Henry and Desmette, 2018) – to outcomes like engagement than focus on opportunities (Rudolph et al , 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…AIHRP refers to specific practical activities in which the organization integrates age-inclusive culture and concept into human resource management elements such as policies, means, and systems that affect employee behavior, attitudes, and performance ( Boehm et al, 2013 ). It is reflected in the inclusive, fair, non-discriminatory, and non-prejudiced treatment of employees of all age groups ( Oliveira and Cabral-Cardoso, 2018 ). Employees of all ages will receive the same level of support from the organization, with equal access to training, skills improvement, and promotion opportunities.…”
Section: Hypotheses Developmentmentioning
confidence: 99%